2001
DOI: 10.1049/ip-gtd:20010258
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric behaviour of polluted porcelain insulators

Abstract: The dielectric behaviour of polluted porcelain insulators is investigated by means of experimental tests and simulation methods. The elaboration of the experimental results, using well known mathematical models of polluted insulators, leads to the identification of the arc constants. It was found out that the arc constants are independent of the insulator type and of the experimental pollution procedure (salt fog or solid layer cool fog method). This allows the formulation of a generalised simulation model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 5 publications
2
43
0
2
Order By: Relevance
“…From the figure 3 it can be observed that present model predicts the flashover voltages with a deviation of less than 10% in comparison with experimentally [15] obtained flashover voltages for Type A, B and C insulators except for Type B insulator the prediction is having a maximum deviation of 21% at lower ESDD levels. Figure 5 shows a comparison of flashover voltages as a function of pollution severity in terms of ESDD (mg/cm 2 ) between experimental [15,38] and proposed model for Type D, E and F Insulators.…”
Section: Validation Of the Modelsupporting
confidence: 51%
See 3 more Smart Citations
“…From the figure 3 it can be observed that present model predicts the flashover voltages with a deviation of less than 10% in comparison with experimentally [15] obtained flashover voltages for Type A, B and C insulators except for Type B insulator the prediction is having a maximum deviation of 21% at lower ESDD levels. Figure 5 shows a comparison of flashover voltages as a function of pollution severity in terms of ESDD (mg/cm 2 ) between experimental [15,38] and proposed model for Type D, E and F Insulators.…”
Section: Validation Of the Modelsupporting
confidence: 51%
“…The proposed model is verified for its validity by comparing the model results with previous researchers experimental and model results [14,15,37,38]. The dimensional details of the insulators considered in the study are given Table 3 Figure 4 shows a comparison of flashover voltages Vs ESDD for Type A, B and C insulators between proposed model and experimental [14].…”
Section: Validation Of the Modelmentioning
confidence: 79%
See 2 more Smart Citations
“…These are typically composed of a central rod made of fibre reinforced plastic and an outer weather shed made of silicone rubber or Ethylene Propylene Diene Monomer rubber (EPDM). The composite insulators replace porcelain insulators because of its excellent anti-pollution performance, economical maintenance, light weight and suitable for highly polluted areas [1][2][3]. To ensure the safe and reliable operation of ac transmission lines, a great number of research on ac flashover performance of polluted insulators have been conducted [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%